Effect of Friction Time on Microstructure and Mechanical Properties of Friction Welded AISI 304 Stainless Steel to AISI 1060 Steel - Ates, H.; Kaya, N. (Металлофизика и новейшие технологии, 2013)
The influence of friction time on the hardness, tensile properties, and microstructure of the welded samples is investigated. With increasing friction time, the hardness and tensile strength values increase too. The hardness of the welding interfaces is higher than that of the base alloys. Microstructures of the welds are examined by the optical and scanning electron microscopy. The results show that all welding joints are perfectly bonded and free of any cracks, pores, and defects. The tensile fracture of welded joint occurred in the AISI 304 side. The chemical composition of the interfaces and deformation zones are detected using energy dispersive spectroscopy. Diffusion of the Cr and Ni is evident on the AISI 1060 side. Досліджено вплив тривалости тертя на твердість, властивості при розтягу та на мікроструктуру зварних зразків. При збільшенні тривалости тертя твердість та границя міцности на розрив також збільшуються. Міцність поверхні зварних контактів виявляється більшою, аніж у основних стопів. Мікроструктуру зварних швів було досліджено методами оптичної й електронної мікроскопії. Показано, що зварні з’єднання були досконало звареними та не мали ніяких тріщин, пор і дефектів. Руйнування при розтягу відбувалося з боку криці AISI 304. Хемічний склад зварних контактів і зон деформації досліджено за допомогою енергодисперсійної спектроскопії. Спостерігалася дифузія Cr та Ni в бік криці AISI 1060. Исследуется влияние времени трения на твёрдость, свойства при растяжении и на микроструктуру сварных образцов. При увеличении времени трения твёрдость и предел прочности на разрыв также увеличиваются. Прочность поверхности сварных контактов оказывается выше, чем у основных сплавов. Микроструктура сварных швов исследуется методами оптической и электронной микроскопии. Показано, что все сварные соединения были идеально сварены и не имели никаких трещин, пор и дефектов. Разрушение при растяжении происходит со стороны стали AISI 304. Химический состав сварных контактов и зон деформации исследуются с помощью энергодисперсионной спектроскопии. Наблюдается диффузия Cr и Ni в сторону стали AISI 1060.